Analysis of the Audience's Reception on Creativity in the 5 Minute Craft Channel on Youtube: Analisis Resepsi Penonton Terhadap Kreatifitas Dalam Channel Kerajinan 5 Menit Di Youtube - Ridwan Hidayat; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2022)
This qualitative study investigates the influence of the 5-Minute Craft YouTube channel on audience creativity through audience reception analysis. Using interview techniques, offline interviews were conducted via WhatsApp to gather responses from viewers. The results reveal a dominant hegemonic position, where the majority of the audience perceives the channel as highly useful. However, a negotiating position emerges, emphasizing the need for verbal guidance to facilitate practical implementation. Conversely, an oppositional stance arises, with some viewers expressing difficulty in applying the crafts shown. Overall, the study highlights the significant impact of YouTube as a mass media platform on audience behavior and sheds light on the complex relationship between content consumption and audience engagement. Highlights: The study investigates the impact of the 5-Minute Craft YouTube channel on audience creativity through qualitative audience reception analysis. The research reveals contrasting audience perspectives, with some perceiving the channel as highly useful while others face difficulties in practicing the crafts shown. The findings emphasize the significant influence of YouTube as a mass media platform on audience behavior and highlight the importance of clear instructional guidance for effective audience engagement. Keywords: Audience reception, Creativity, YouTube channel, Qualitative research, Media influence